Struktur Komunitas Mikroalga di Wisata Air Umbul Kabupaten Klaten - Murti, Ruth Karisma; Nurmiyati, Nurmiyati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2025)
Microalgae give an idea of the fertility of a body of water because the more microalgae in a body of water, the more fertile the water is. This research aims to determine the structure of the microalgae community in the Umbul water tourism area of Klaten Regency. This type of research is descriptive quantitative with a survey method. The data collection technique uses purposive sampling with hand-collection techniques. The data analysis technique uses the Shanon-Wiener diversity index (H'), species evenness index, dominance index, and species richness index as well as looking at physical and chemical parameters to determine water quality. The most common microalgae come from the Bacillariophceae and Cyanophyceae classes.The Shannon-Wiener diversity index for the three stations is in the stable category but the highest index value is at station III at 2.860 and the lowest index value at station I is 2.427. The highest species evenness index was at station I, namely 0.864, and the lowest index at station II was 0.764, so the species evenness index was stable. The highest Dominance Index at station II is 0.13 but is still close to 0 so the dominance index is low. The highest species richness index was at station III and the lowest at station II was 4.83. According to the results of the Umbul Nilo diversity index, Umbul Ponggok and Umbul Sigedang are included in the unpolluted category